Ājādī para uṭhate savāla, nālī para mocī : [Banārasa śahara ke sandarbha meṃ] - Manju Devi (Rādhākr̥shṇa Prakāśana, 2009)
Study on social and economic conditions of shoemakers in Vārānasi, Uttar Pradesh, India.